Development Of Student Attendance System Application Using Qr Code At MAN 1 Kota Gorontalo - Styefani, Ayu; Utomo, Pramudi (Ridwan Institute, 2025)
Manual paper-based attendance systems are still prevalent in many madrasahs. This study aims to: (1) develop a QR Code-based student attendance system at MAN 1 Kota Gorontalo, (2) test the system's performance, and (3) determine its feasibility. This research and development (R&D) study employs the Waterfall model, encompassing the stages of Analysis, Design, Implementation, Verification, and Maintenance. The subjects were 33 teachers. Product trials were designed in three parts: testing by system experts, operational testing, and user testing. The system's quality was evaluated based on ISO 25010 and Olsina et al. standards, covering functional suitability, usability, performance efficiency, reliability, and maintainability. Data were collected through questionnaires and observations. Questionnaires gathered data on functional suitability, usability, and customer intimacy, while observations collected data on performance efficiency and reliability. Data analysis used quantitative descriptive techniques. The results are: (1) a functional web-based student attendance system using QR Code, (2) the product met quality standards, receiving the predicates